An Extended Analytical Overview of the CEFR System from A1 to C2 - Ro'ziboyeva Dilshoda; Xolmatova Gavhar (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article provides a comprehensive analytical overview of the Common European Framework of Reference for Languages (CEFR) from A1 to C2. It examines language competencies, assessment criteria, and practical applications at each proficiency level. CEFR serves as a universal benchmark for curriculum design, learner placement, and international language assessment, supporting effective language teaching and learning across academic, professional, and social contexts.